CIP: Promoting potatoes - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Based in Peru, the International Potato Center (CIP) now has three offices in Africa to support the rapidly increasing cultivation of this crop on this continent. In certain regions, potatoes are even tending to replace cereals, especially during...